Phthisiatry: textbook for high education students enrolled in speciality "Medicine", "Medical-preventive work" in the training direction "Phthisiatry" - Кошечкин, В. А. фтизиатрия 19391119 Владимир Анатольевич (Textbook, 2017)
In the textbook "Phthisiatry" basic information is presented on etiology, clinical picture, diagnostics, methods of treatment, prevention of TB in accordance with the tuberculosis program of the medical schools adopted by the Federal state educational standard of higher professional education (specialty 060101). Special attention is devoted to current important issues of TB: drug-resistance and tuberculosis/HIV coinfection. The textbook assembled in Russian and English in separate editions. Exposition of the basic materials in two languages has diff erent goals. For foreign students who are learning phthisiatry in English to help to obtain the material in Russian language. For foreign students studying phthisiatry in Russian to give the opportunity to understand material more deeply. For Russian students to give the opportunity for perfection of their English, which is the language for professional communication in international medical forums. The textbook is designed for medical students.